Acute Toxicity of Herbicides and Sensibility of Aquatic Plant Wolffia brasiliensis as a Bioindicator Organism - PEREIRA,P.C. (2019)
ABSTRACT: This study aimed to establish the mass cultivation of Wolffia brasiliensis under laboratory conditions, determine the sensitivity of reference substances (potassium dichromate, sodium chloride, and potassium chloride), and estimate the acute toxicity (LC50;7d) for the herbicide glyphosate, diquat, paraquat, imazapyr, 2,4-D, saflufenacil, imazamox, penoxsulam, metsulfuron-methyl, and atrazine. Three media were tested for culture establishment: Hoagland’s medium, 5.0 g L-1 NPK fertilizer (20-5-20), a mixture of Oxisol + organic substrate of decaying aquatic plant (2:1; v v-1). Sensitivity tests with reference substances and acute toxicity for herbicides were carried out after establishing the cultivation. The species W. brasiliensis presented an excellent sensitivity response to reference substances, with means of LC50;7d of 15.61±2.13 g L-1, 17.02±0.50 g L-1, and 52.54±4.27 mg L-1 for sodium chloride, potassium chloride, and potassium dichromate, respectively. The acute toxicity response indicated that W. brasiliensis was extremely sensitive to diquat (LC50;7d = 0.07 mg L-1) and paraquat (LC50;7d < 0.05 mg L-1), sensitive to imazapyr (LC50;7d = 21.10 mg L-1), and little sensitive to the other herbicides. The response capacity for the different groups of herbicides, the standardized response to reference substances, and ease of cultivation in the laboratory indicate the potential for using this aquatic plant in the assessment of herbicide risk in aquatic environments.